Influence of device deposition techniques on the process optimization of CdZnTe thin-film matrix using charge-based analysis. (1st August 2020) - Haider, Ijlal; Khan, Basit; Ali, Muhammad; Shuja, Ahmed; Qureshi, Asad Farooq; Ali, Zulfiqar
Abstract: –Cadmium Zinc Telluride (CZT) is tertiary semiconductor material that has numerous applications in photonics, Opto-electronics, and photovoltaics due to its tunable direct band gap of 1.4eV–2.26eV. This bandgap can be altered by varying the elementary concentrations of Cadmium Telluride (CdTe) and Zinc Telluride (ZnTe). There are several different techniques that are used to grow CZT on different substrates. In this study, we have employed two different techniques, Electron Beam Evaporation (E-Beam) process and Resistive Heating (R-Heating) technique, and investigated the variance in the electrical characteristics of CZT matrixes fabricated by these two techniques. We have grown 1 μm thick Cd1 -x Znx Te (x = 0, 0.25, 0.5, 0.75, 1) thin films and performed comparative analysis of each sample with its respective growth technique. After fabrication we have analyzed Current Voltage (I–V), Charge Deep Level Transient Spectroscopy (Q-DLTS), Transient of Photo-voltage (TPV), trap analysis for the determination of overall activation energy, deep level traps and their locations within the energy band picture, trap assisted capture cross sections, deep level trapping densities, their comparative ratios (I R-Heating /I E-beam ) and provided their comparative nurture case wise. Our analysis revealed that ZnTe sample are least effected by the deposition technique whereas CdTe samples are most effected when deposited by different techniques. We have found that trap centers are present in each fabricated sample and all are above the fermi level. The trap level placed nearer to the conduction band edge has higher capture cross sections than those placed far from the conduction band edge. Trap level energies are ranging from this to this with capture cross sections of this to this, respectively. The trap centers are also requalified from the TPV measurements i.e. lower trap energies provide higher potential and vice-versa.